2022
DOI: 10.1093/oncolo/oyac072
|View full text |Cite
|
Sign up to set email alerts
|

PCM1-JAK2Fusion Tyrosine Kinase Gene-Related Neoplasia: A Systematic Review of the Clinical Literature

Abstract: Background This review summarizes the case studies of PCM1-JAK2 fusion tyrosine kinase gene-related neoplasia. Recommended treatment includes JAK2 inhibitors and hematologic stem cell transplantation (HSCT), although the small number of patients has limited study of their efficacy. Herein, we present all available cases in the current searchable literature with their demographics, diagnoses, treatments, and outcomes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…( 35 ) in a patient suffering from a rare, aggressive myeloid neoplasia with eosinophilia; treatment with futibatinib , an oral selective small molecule inhibitor of FGFR1-4, resulted in complete hematologic and cytogenetic remission ( 35 ). The PCM1 gene as partner in the chimera PCM1::JAK2 has been implicated in the pathogenesis of also other acute myeloid/lymphoid neoplasms ( 36 ) whereas rearrangements of FGFR1 are rare ( 37 ). The use of selective TKIs can potentially affect outcomes in these patients ( 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 35 ) in a patient suffering from a rare, aggressive myeloid neoplasia with eosinophilia; treatment with futibatinib , an oral selective small molecule inhibitor of FGFR1-4, resulted in complete hematologic and cytogenetic remission ( 35 ). The PCM1 gene as partner in the chimera PCM1::JAK2 has been implicated in the pathogenesis of also other acute myeloid/lymphoid neoplasms ( 36 ) whereas rearrangements of FGFR1 are rare ( 37 ). The use of selective TKIs can potentially affect outcomes in these patients ( 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…For cases with PCM1::JAK2 fusion, the disease course can be highly variable. 22,74 In patients presenting in chronic phase of a myeloid neoplasm, the disease may be indolent with a 5-year survival up to 80%. 14,22,74 On the other hand, in patients who present or progress to acute leukemia, the prognosis is dismal.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…22,74 In patients presenting in chronic phase of a myeloid neoplasm, the disease may be indolent with a 5-year survival up to 80%. 14,22,74 On the other hand, in patients who present or progress to acute leukemia, the prognosis is dismal. Targeted therapy with JAK2 inhibitors such as ruxolitinib may offer some but limited benefit 24,75 and should be used to bridge patients to allogeneic SCT, which can lead to durable disease-free survival.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…The reason for the male preponderance is not clear. 8 Lierman et al, number of patients reported precludes a definitive statement regarding its effect on survival. Further studies are needed to determine how best to utilize ruxolitinib.…”
mentioning
confidence: 99%
“…Therefore, currently, ASCT is still the only way to cure the disease, particularly in the absence of acute leukemia. 8 For those patients who are unsuitable for transplantation, the prospect seems very bleak. Some patients with MPN received hydroxyurea or interferon for initial treatment and then followed a strategy of watch and wait.…”
mentioning
confidence: 99%